Perish from the earth - Putnam, Jonathan F. (Putnam, Jonathan F. Lincoln and Speed mystery., 2017)
"A murder aboard a steamboat forces Abraham Lincoln to make a fateful choice--one on which the future of the nation may hang, if his client doesn't first--" -- provided by publisher.